Domestic spheres recreating space from the fragments of experience - David, Nadya Melina C. (2013)
This project is anchored on the idea that we leave traces or imprints in our domestic spaces as we go about our daily lives. These traces are the variegated remnants of everyday life; practice, rituals, activities, interactions, movements and ideas. As Walter Benjamin states, ?to live means to leave traces?. Our body language and posture; the way we cross our legs and position our body as well as the way we speak, our choice of language and our ideas determine the openness and closeness of the spaces about us. But then the ways we perceive our spaces are also mediated through our bodily senses. The particular scent of a room can transport us to a childhood memory, the sound or music we hear, the texture of the walls and other visual stimulants shape our perception of the spaces that we encounter in our daily lives. In this perspective, the individual body becomes central in the exploration of space as it is manifested in the signs and traces of human experience. Domestic Spheres is a process-based work that represents and simulates these manifestations of human experience. My bachelor?s degree in interior design, gave me a command of 3-dimensional space and an ontological view of space as an empty box or a blank canvas passively waiting for the artist to give it life. This view is what contemporary spatial planners are now trying to change as we try to understand and decode the ever evolving complexities of urban life. The objects we bring into our home, the scented candles we use to permeate the air, the food inside our refrigerators and even our clutter are all signs of inhabitation and clues about the inhabitant. Domestic Spheres operates in the concept that the traces of human experience and our interactions with space may be understood as a continuous reproduction of patterns just as every living creature in the world creates patterns in nature. To understand the pattern in something that seems unfamiliar and chaotic, is to find order and decode its underlying structure. Therefore, to use patterns as a means of making sense of our continually evolving domestic spaces, is to understand the individual body, our social interactions and everyday life experiences. By linking the components of printmaking; material, process, physicality and multiplicity, with the practice of everyday life rituals, my intention is to create a visual metaphor of the dialogue and metamorphosis of the forms, patterns and traces we leave as we live which ultimately presents a simulation of the processes involved in the production of spaces. It is a project that proposes a visual re-presentation of domestic space and everyday life beyond the physical dimensions and the traditional depiction in genre paintings. To achieve this, I performed the activity of relief printing as a daily ritual just as eating, sleeping, walking and talking, to name a few, are part of my everyday domestic life. I used my actual living space not only as a studio space but also as the primary material or support by printing directly on every available surface within my domestic space, i. e. walls, floor, ceiling, furniture and furnishings. Ultimately, my domestic space also served as a museum or gallery space as it is re-presented through fragments of my everyday life; rituals, ideas, interactions and experiences.
"May 2013."
Thesis (M.A. Fine Arts)--University of the Philippines, Diliman.
Keywords: Domestic space in art; Relief (Art) -- Exhibitions; Prints -- Technique